Association between education and depressive symptoms among community-dwelling older adults in Iceland. The AGES-Reykjavik Study. - Chiharu Nishizuka 1985- (2022)
Background: Education is a major indicator of social status. Previous studies have suggested that a higher education level has a positive impact on one's health literacy and health behaviors throughout life. This study aimed to examine the association between education and depressive symptoms among community-dwelling older adults aged 65 years and older in Iceland. Method: As a cross-sectional study using data from the Age, Gene/Environment Susceptibility-Reykjavik Study (AGES-RS) cohort (n = 3,989, mean age = 76.2, 56.3% women), education in this study was classified into four levels: primary (n = 895), secondary (n = 1,980), college (n = 630), and university (n = 484). For the analysis, education was categorized into two groups: primary education versus higher education (secondary, college, and university). Depressive symptoms were assessed by using the 15-item Geriatric Depression Scale (GDS). High depressive symptoms (HDEPS) were defined if the GDS score was 6 or higher. Logistic regression analysis was performed to examine the association. Results: Education was significantly associated with the GDS score (p < .001). Compared to people with primary education, those with higher education were significantly less likely to have HDEPS after adjusting for confounders including age, gender, body mass index, physical activity, coronary disease (diabetes, hypertension), and smoking status (odds ratio [OR] = 0.04, 95% confidence interval [CI] 0.01–0.15). Conclusion: Older adults with higher education were less likely to have HDEPS compared to those with primary education in the current cross-sectional analysis, indicating that education is highly associated with depressive symptoms of community-dwelling older adults in Iceland. This outcome indicates that education level among older adults can be an important indicator of mental health status and lifestyles in the screening process in primary care. Public health authorities then need to develop and strengthen health services to ensure that the disadvantaged older ...